Prior Knowledge, Episodic Control and Theory of Mind in Autism: Toward an Integrative Account of Social Cognition - Zalla, Tiziana; Korman, Joanna (Frontiers in Psychology, 2018)
Over the last thirty years, research has explored the Theory of Mind (ToM), the ability to attribute mental states to oneself and to others. Work on ToM in typical and atypical populations has shed light on the neurocognitive mechanisms underlying social understanding and interaction. The ToM hypothesis has long been regarded as a comprehensive explanation of the severe cognitive and behavioral impairments encountered by individuals with autism. However, high-functioning individuals can often pass both first-order and second-order false belief tasks using cognitive compensation strategies. To provide more sensitive measures of mental state attribution abilities, researchers have introduced more difficult, “advanced” theory of mind tasks. In this article, we argue that in attempting to bypass compensation strategies, these new advanced ToM tasks, such as the Faux Pas and the Strange Stories tasks, impose cognitive demands beyond those specific to the domain of ToM. We then provide an integrative account of social deficits in autism that takes into account several distinct components of mental state understanding, including both general cognitive capacities and processes specific to ToM. We argue that a number of related cognitive abilities, including episodic cognitive control and inferencing from prior knowledge, are necessary to understand how both people with autism and typical development navigate challenging, real-life social situations.